Gene therapy in treating sickle cell anemia disease - Dol Ramli, Nur Amira; Abdul Hadi, Muhammad Faris; Mohamed, Elizah; Mohd Fauzi, Noor Akhmazillah (Penerbit UTHM, 2022)
Sickle cell anemia disease or in short known as SCD is an inherited and serious condition affecting the body's blood and various organs. This disease can give effects to the red blood cells that can cause sickle-like episodes that cause pain and other symptoms. People with SCD are generally well in between episodes of sickling which may cause a long term of complications. Certain situations may trigger sickling, like cold, low oxygen levels, infection or lack of fluid in the body (dehydration). This complication of disease can be prevented from the root with a good treatment. Therefore, early diagnosis and specialized treatment for SCD are recommended from doctors. Based on the previous research, the method used in treating this disease is stem cell transplantation that can be found in bone marrow. Actually, every transplant of bone marrow has risks and bad effects on the patient. It can give an infection to the immune system like attack the new stem cells that will cause failure to the transplant. Moreover, once the stem cell of the donor doesn't match with the recipients, the new immune system cell of donors would attack a few organs of recipients. So, these complications are very dangerous to the donors and recipients. Based on the medical biotechnology that has a lot of benefits, this research will focus on treating disease by gene therapy with CRISPR/Cas9 as a method and an adeno-associated virus (AAV) as a vector. In this research which is based on application of biotechnology, it will be focusing on gene therapy. Gene therapy is also one of the best treatments for this disease. The main reason for patients with sickle cell is causing the disorder of the adult hemoglobin gene, not the fetal hemoglobin gene during the gene mutation. So, this gene therapy in the sickle cell operates by growing the production of the selected gene by restoring the transition performance again to fetal hemoglobin, which does not sickle, and subsequently decreasing sickle hemoglobin and thereby increasing fetal hemoglobin.